Building effective school–community partnerships in Aboriginal remote school settings. Issue 2 (30th December 2021) - Gower, Graeme; Ferguson, Cath; Forrest, Simon
Abstract: The benefits of school and community partnerships are well documented in government reports and the academic literature. A number of government initiatives have been introduced to actively involve parents and the community in school matters. In addition, various agencies have produced resource kits and guidelines to assist schools and communities to develop and foster partnerships, and partnership agreements. Much of this study has focused on working with Aboriginal peoples. The use of the term, 'Aboriginal' in this paper refers to Aboriginal and Torres Strait Islander people. Initiatives such as 'What Works' have had some success in building strong Aboriginal community and school partnerships, however, the literature also reveals that despite such initiatives, the levels of success vary from school to school, with some partnerships unable to develop or be sustained. In responding to a gap in the current knowledge, the authors examine the value of school–community partnerships in a rural and remote school where the percentage of Aboriginal Australian students is high. A brief summary of the outcomes of some of the major initiatives with aims to build effective school and community partnerships is provided. This is followed by the findings from a small pilot research study on the implementation of initiatives to build strong school–community relationships in rural and remote Indigenous school settings in Western Australia. The challenges that may inhibit the establishment of successful school–community relationships/collaboration are discussed and suggestions provided on how these challenges can be addressed.